Studies on Nanocomposites of Polyaniline and Zinc Oxide Nanoparticles with Supporting Matrix of Polycarbonate. (4th October 2012) - Ansari, Shahid Pervez; Mohammad, Faiz
Abstract : Nanocomposites of polyaniline and zinc oxide nanoparticles using polycarbonate as supporting matrix were prepared by direct mixing process. These nanocomposites were studied for their DC electrical conductivity using four-in-line probe technique. Stability of DC electrical conductivity in terms of electrical conductivity retention was also studied using two slightly different techniques. The nanocomposites were also characterized using FTIR, SEM, TEM, and XRD. It was found that the electrical conductivity of the nanocomposites first increased with the increase in concentration of ZnO nanoparticles content, but then decreased on further increase in its content. Stability studies showed that the loss in electrical conductivity decreased with increase of ZnO content in nanocomposites. TEM and XRD results showed that nanoparticles are uniformly distributed in polymer matrix and also suggest that the direct solution mixing method may be adopted as an easy and efficient route for the preparation of nanocomposites.